Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1007/s13593-017-0466-2
|View full text |Cite
|
Sign up to set email alerts
|

Wood vinegar seed priming improves yield and suppresses weeds in dryland direct-seeding rice under rainfed production

Abstract: A declining farm labor force and increasing water scarcity worldwide are forcing rice farmers to adopt directseeding rice production. Under this production system, speed of germination, field emergence, and crop yield depend prominently on rice seed vigor. We hypothesized that seed priming can enhance rice seed vigor and agronomic performance. The objective of this study was to evaluate the effect of GA 3 and wood vinegar seed priming on seed vigor, seedling performance, and grain yield in farmer's fields. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 20 publications
2
15
0
Order By: Relevance
“…Many compounds have been used successfully as SPAs. Salicylic acid, acetylsalicylic acid, and glycinebetaine promoted germination in carrots [ 22 ], 5-hydroxybenzimidazole increased yields and stress resistance in tomatoes [ 23 ], and pyroligneous acid increased yields in rice [ 24 ]. Several naturally occurring antioxidants, such as lycopene, β-carotene, and ascorbic acid (AsA), also increased tomato dry mass and photosynthesis when used as SPAs [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many compounds have been used successfully as SPAs. Salicylic acid, acetylsalicylic acid, and glycinebetaine promoted germination in carrots [ 22 ], 5-hydroxybenzimidazole increased yields and stress resistance in tomatoes [ 23 ], and pyroligneous acid increased yields in rice [ 24 ]. Several naturally occurring antioxidants, such as lycopene, β-carotene, and ascorbic acid (AsA), also increased tomato dry mass and photosynthesis when used as SPAs [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, research on WD has focused on studying its antioxidant, plant growth regulating, bacteriostatic, and soil additive effects on crops and plants of food interest, with particular attention for the environment. It has also been reported that the application of WD can promote plant growth (Simma et al, 2017), increasing the content of mineral and nutritional elements in the soil (Polthanee et al, 2014). Furthermore, the acidic nature of WD can regulate soil pH (Lashari et al, 2015), improve nutrient availability (Lashari et al, 2013), inhibit ammonium loss (Grewal et al, 2018), mitigate N 2 O and CH 4 emissions (Sun et al, 2018), and influence the soil microbial community (Cardelli et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Wood distillate (WD) is widely recognized as a promising multifunctional amendment in agriculture (Simma et al., 2017). WD, also known as pyroligneous acid or wood vinegar, is a by‐product originated from the condensation of gases during B production (Grewal et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The most abundant substance (about 50%) is acetic acid, which gives PA its characteristic pH below 3, while the phenolic group gives it a smoky smell [ 19 ]. Recently, researchers have begun to study the possible uses of PA in agriculture, highlighting an increase in yield, product quality, and plant health [ 23 , 24 ], improvement of germination and seed growth [ 25 , 26 , 27 ], resistance to fungal pathogens [ 28 , 29 ], resistance to exposure to high concentrations of ozone [ 30 ], an increase in nitrogen concentration in the soil [ 31 ], and resistance to stress, disease, and insects [ 32 ]. PA inhibits the growth of fungal mycelium due to its negative effects on the speed of division, cell membranes, electrolytes, and protein synthesis [ 28 ].…”
Section: Introductionmentioning
confidence: 99%